2013
DOI: 10.1016/s0187-6236(13)71064-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weather types on hospital admissions for respiratory diseases in Castilla-La Mancha, Spain

Abstract: El objetivo de este estudio consiste en evaluar la relación entre el riesgo de ingreso hospitalario por enfermedades respiratorias habidos en hospitales de Castilla-La Mancha, España, y los tipos diarios de masas de aire (situaciones meteorológicas) presentes durante el periodo 2000-2006, utilizando un enfoque climatológico sinóptico. Se determinaron los principales tipos de circulación atmosférica presentes en la zona para el invierno y la primavera (estaciones en que las admisiones hospitalarias de carácter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…In this time-series analysis, to account for the great data variability encountered on the different week days (Faryar 2013 ; De Pablo Dávila et al 2013 ; Sun et al 2009 ; Tai et al 2006 ), we normalized the data sample per week day, season, and bank holidays, calculating a ratio of observed number of patients by mean number of patients in the particular day of the week, or holiday. In addition, and specifically for the analysis explained in the “ Cardiovascular and respiratory test ” section below, 7-day averages for weather and air pollution data have been used and holiday periods and bank holidays have been omitted from the sample.…”
Section: Methodsmentioning
confidence: 99%
“…In this time-series analysis, to account for the great data variability encountered on the different week days (Faryar 2013 ; De Pablo Dávila et al 2013 ; Sun et al 2009 ; Tai et al 2006 ), we normalized the data sample per week day, season, and bank holidays, calculating a ratio of observed number of patients by mean number of patients in the particular day of the week, or holiday. In addition, and specifically for the analysis explained in the “ Cardiovascular and respiratory test ” section below, 7-day averages for weather and air pollution data have been used and holiday periods and bank holidays have been omitted from the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have shown that the exposure to atmospheric pollutants also has an effect on the circulatory system. De Pablo et al [8] found positive and statistically significant associations between variations in concentration levels of SO 2 , O 3 and NO 2 with morbidity, mainly for people older than 69 years. This association was greater for cardiovascular type diseases than for respiratory.…”
Section: Introductionmentioning
confidence: 98%
“…El aumento en la concentración de partículas PM 10 y ozono están relacionadas con el incremento en la tasa de mortalidad prematura, daño a la vegetación y edificios, así como la reducción de la visibilidad (HEI, 2000;O'Neill et al, 2004 a, b;De Pablo et al, 2006;Filleul et al, 2006;Ritz et al, 2006;Zhang et al, 2006). Las fracciones que representan un mayor riesgo para la salud son las PM 10 y PM 2.5 , las cuales por su tamaño pueden penetrar a la región torácica y ser tóxicas (Pope et al, 1995).…”
Section: Introductionunclassified